2017
DOI: 10.1109/tnb.2017.2714462
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Force Microscopy in Characterizing Cell Mechanics for Biomedical Applications: A Review

Abstract: -Cell mechanics is a novel label-free biomarker for indicating cell states and pathological changes. The advent of atomic force microscopy (AFM) provides a powerful tool for quantifying the mechanical properties of single living cells in aqueous conditions. The wide use of AFM in characterizing cell mechanics in the past two decades has yielded remarkable novel insights in understanding the development and progression of certain diseases, such as cancer, showing the huge potential of cell mechanics for practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(59 citation statements)
references
References 170 publications
(240 reference statements)
0
55
0
4
Order By: Relevance
“…This system combines key features comparable to other leading techniques, with a regular array of probes that can map the mechanical response, as is possible with atomic force microscopy (22,(63)(64)(65), and measure cellular fluctuations and local rheology simultaneously with high temporal resolution and ligand specificity, as with magnetic twisting cytometry (4,44,45). In this study, the use of AMPADs has allowed us to make a detailed examination of the mechanics of the cell cortex and stress fibers.…”
Section: Discussionmentioning
confidence: 99%
“…This system combines key features comparable to other leading techniques, with a regular array of probes that can map the mechanical response, as is possible with atomic force microscopy (22,(63)(64)(65), and measure cellular fluctuations and local rheology simultaneously with high temporal resolution and ligand specificity, as with magnetic twisting cytometry (4,44,45). In this study, the use of AMPADs has allowed us to make a detailed examination of the mechanics of the cell cortex and stress fibers.…”
Section: Discussionmentioning
confidence: 99%
“…械特性提供了新的工具. 与光镊 [17] 、磁镊 [18] 、微流 控 [19] 、微管吸取 [20] 等单细胞机械特性测量技术相比, AFM的优势是具有纳米级的空间分辨率, 且能够同时 获取细胞表面形貌信息以及机械特性信息 [21] , 有助于 研究细胞结构与细胞机械特性以及细胞生理功能之间 的关联. 过去的20年中, 研究人员利用AFM对细胞机械 特性开展了广泛的研究 [22~24] , 揭示了细胞骨架蛋白对 细胞弹性的决定作用 [25,26] , 阐明了癌细胞与正常细胞机 械特性之间的显著差异 [27~29] 以及细胞机械特性与细胞 侵袭能力之间的密切关联 [30~32] , 证明了细胞机械特性 是一个可有效指示细胞生理病理变化的生物指标 [33,34] .…”
Section: 原子力显微镜(Afm)的发明为探测单个细胞的机unclassified
“…[17][18][19][20] AFM is useful to characterise the changes in cells to identify proles that could indicate the development of a disease or even support the diagnosis. [21][22][23][24] Recently, it was reported that the high cigarette-consumption increased membrane roughness of RBC due to changes on its surface. 25 Biophysical changes at the cellular level should also include the evaluation of chemical alterations that cause them.…”
Section: Introductionmentioning
confidence: 99%